A flexible zinc-ion battery type self-powered pressure sensor and a preparation method thereof

CN117804641BActive Publication Date: 2026-10-27HEBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410002319.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-02
Publication Date
2026-10-27
Estimated Expiration
2044-01-02

AI Technical Summary

Technical Problem

这种电池式传感策略可以解决当前压电和摩擦电自供电压力传感器通常只能检测动态压力的局限性

Benefits of technology

[0023]1、本发明在制备柔性电极过程中先在柔性基底上先涂覆中间亲和层油墨,之后再涂覆正/负极油墨,使得制备的电极具有优异的柔顺性和机械性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117804641B_ABST
    Figure CN117804641B_ABST
Patent Text Reader

Abstract

The application provides a flexible zinc ion battery type self-powered pressure sensor and a preparation method thereof, the sensor comprising a positive electrode layer, a gel electrolyte layer, a self-supporting negative electrode layer, a separation layer and a third electrode layer arranged in sequence, the separation layer being located between the self-supporting negative electrode layer and the third electrode layer, so that when there is no external mechanical pressure, the whole circuit is in an open circuit state and cannot output an electric signal; when the external mechanical pressure increases, the interface resistance of the whole circuit and the resistance of the separation layer decrease, so that the conversion from a mechanical signal to an electric signal is realized. The zinc ion battery type integrated self-powered pressure sensor provided by the application combines self-power supply, chargeable and dischargeable and excellent pressure sensing performance, and in addition, the sensing strategy can overcome the limitation that current piezoelectric and triboelectric self-powered pressure sensors can only detect dynamic pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sensor technology, and in particular relates to a flexible zinc-ion battery-type self-powered pressure sensor and its preparation method. Background Technology

[0002] With the advent of the Internet of Things (IoT) era, numerous sensor nodes are distributed throughout the network to capture, process, and transmit various sensory information, finding new applications in personalized healthcare management, human-computer interaction, smart homes, and environmental monitoring. Simultaneously, there is increasing emphasis on research into flexibility and lightweight design. Accurate and continuous pressure signal detection without an external power source is a key technology for miniaturizing wearable electronic devices. Currently, most wearable flexible sensing devices require cumbersome wiring and external power supplies, limiting the further development of smart electronic devices. While piezoelectric and triboelectric sensors can achieve self-powered pressure sensing without an external power source, they typically can only detect dynamic signals and cannot maintain a continuous signal output under static pressure. This limits their application in static pressure detection. Therefore, developing a new sensing mechanism or sensor is crucial for monitoring static mechanical stimuli without an external power source. Summary of the Invention

[0003] In view of this, the present invention aims to overcome the shortcomings of the prior art by developing a flexible zinc-ion battery-based self-powered pressure sensor through structural design, material selection, and fabrication processes. This sensor is based on a flexible battery and achieves pressure detection by introducing an insulating layer. The battery-type sensor can serve as both an excellent self-powered wearable pressure sensor and a battery, combining the advantages of both. This battery-based sensing strategy overcomes the limitation of current piezoelectric and triboelectric self-powered pressure sensors, which typically only detect dynamic pressure.

[0004] To achieve the above objectives, the technical solution of the present invention is implemented as follows:

[0005] A flexible zinc-ion battery-type self-powered pressure sensor includes a positive electrode layer, a gel electrolyte layer, a self-supporting negative electrode layer, an isolation layer, and a third electrode layer. The gel electrolyte layer is located between the positive electrode layer and the self-supporting negative electrode layer, the isolation layer is located between the self-supporting negative electrode layer and the third electrode layer, and the self-supporting negative electrode layer is disposed below the isolation layer.

[0006] Furthermore, the positive electrode layer is at least one of copper foil, capacitive electrode material ink coated on a conductive current collector, or metal oxide ink coated on a conductive current collector. The capacitive electrode material is at least one of activated carbon (AC), carbon nanotubes (CNTs), graphene, and carbon fiber. The metal oxide is at least one of MnO2, RuO2, and V2O5. The conductive current collector is at least one of stainless steel foil, stainless steel mesh, and flexible conductive elastomer substrate.

[0007] Furthermore, the self-supporting negative electrode layer is a flexible self-supporting zinc negative electrode.

[0008] Furthermore, the isolation layer is an electrospun fiber film or a porous sponge foam with a thickness of (0.2 mm to 2 mm).

[0009] This invention also provides a method for fabricating a flexible zinc-ion battery-type self-powered pressure sensor, comprising the following steps:

[0010] (1) Preparation of intermediate affinity layer ink;

[0011] The conductive carbon black and multi-walled carbon nanotubes were ground and then poured into waterborne polyurethane and stirred. The weight ratio of conductive carbon black, multi-walled carbon nanotubes and waterborne polyurethane was (0.5~2):1:(1.5~3.5).

[0012] (2) Preparation of the positive electrode layer;

[0013] First, the positive electrode ink is prepared by grinding conductive carbon black, multi-walled carbon nanotubes, and manganese dioxide. Then, it is poured into a mixed solvent composed of aqueous polyurethane, TOCNF aqueous solution, and isopropanol and stirred. The weight ratio of conductive carbon black, multi-walled carbon nanotubes, and manganese dioxide is 1:1:(5.5-9.5), and the volume ratio of aqueous polyurethane, TOCNF aqueous solution, and isopropanol is (1-2.5):(4-6):(8-12). The weight ratio of conductive carbon black, multi-walled carbon nanotubes, manganese dioxide, and mixed solvent is 1:1:(5.5-9.5):(93-110). Next, the mold is prepared by placing a high-temperature resistant polyester film (PET) into a laser cutting machine to process the mold into the required shape. A piece of flexible substrate is cut off, and the PET mold is tightly attached to the flexible substrate. Then, the intermediate affinity layer ink is poured into the mold prepared from PET. After vacuum heating in a drying oven, the positive electrode ink is poured on the intermediate affinity layer and vacuum heating is continued in the drying oven.

[0014] (3) Preparation of a self-supporting negative electrode layer;

[0015] First, the negative electrode ink is prepared by grinding conductive carbon black, multi-walled carbon nanotubes, and zinc powder, and then stirring them in a solvent composed of aqueous polyurethane, TOCNF aqueous solution, and isopropanol. The weight ratio of conductive carbon black, multi-walled carbon nanotubes, and zinc powder is 1:1:(9.5-25), and the volume ratio of aqueous polyurethane, TOCNF aqueous solution, and isopropanol is (1-2.5):(4-6):(8-12). The weight ratio of conductive carbon black, multi-walled carbon nanotubes, zinc powder, and mixed solvent is 1:1:(9.5-25):(93-110). Next, a mold is prepared by processing a high-temperature resistant polyester film (PET) into the required shape using a laser cutting machine. A piece of flexible substrate is cut off, and the PET mold is tightly bonded to the flexible substrate. Then, the intermediate affinity layer ink is poured into the mold prepared from PET. After vacuum heating in a drying oven, the negative electrode ink is poured onto the intermediate affinity layer, and vacuum heating continues in the drying oven.

[0016] (4) Preparation of gel electrolytes;

[0017] PVA, zinc chloride, ethylene glycol and graphene oxide solution were poured into deionized water and stirred in a 95°C water bath for 2 hours.

[0018] (5) Fabrication of the third electrode layer;

[0019] The intermediate affinity layer ink is poured into a mold made of PET and then vacuum heated in a drying oven;

[0020] (6) Place the third electrode layer, the isolation layer, the self-supporting zinc negative electrode layer, the gel electrolyte layer and the positive electrode layer in sequence from top to bottom, and encapsulate them by coating the edges of each part with a semi-cured PDMS solution.

[0021] The present invention also provides an application of a flexible zinc-ion battery-type self-powered pressure sensor in wearable devices.

[0022] Compared with existing technologies, the flexible zinc-ion battery-type self-powered pressure sensor and its fabrication method described in this invention have the following advantages:

[0023] 1. In the process of preparing flexible electrodes, the present invention first coats an intermediate affinity layer ink on a flexible substrate, and then coats positive / negative electrode inks, so that the prepared electrode has excellent flexibility and mechanical properties.

[0024] 2. This invention uses a novel strategy to prepare the sensor by introducing an isolation layer between the self-supporting negative electrode and the third electrode. This avoids the limitations in sensor preparation caused by the adhesiveness or liquid content of the gel electrolyte. Furthermore, the introduced porous sponge foam gives the sensor a wide detection range.

[0025] 3. The battery-powered sensor of this invention can serve as both an excellent self-powered wearable pressure sensor and a battery, combining the advantages of both. This battery-based sensing strategy overcomes the limitation of current piezoelectric and triboelectric self-powered pressure sensors, which typically can only detect dynamic pressure. Attached Figure Description

[0026] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0027] Figure 1 This is a schematic diagram of the flexible zinc-ion battery-type self-powered pressure sensor structure in an example of the present invention.

[0028] Figure 2 This is a schematic diagram of the flexible electrode fabrication process in an example of the present invention.

[0029] Figure 3 This is a physical diagram of a self-supporting negative electrode in an example of the present invention.

[0030] Figure 4 The image shows a physical representation of the flexible electrode and sensor used in an example of this invention.

[0031] Figure 5 This is a schematic diagram illustrating the stability test of the flexible zinc-ion battery-type self-powered pressure sensor in an example of the present invention.

[0032] Figure 6 This is a schematic diagram of the voltage signal of the flexible zinc-ion battery-type self-powered pressure sensor in this invention at different finger bending angles.

[0033] Figure 7 This is a schematic diagram of the voltage signal of the flexible zinc-ion battery-type self-powered pressure sensor in this invention at different bending angles of the wrist.

[0034] Figure 8 This is a schematic diagram showing the electrochemical performance of the flexible zinc-ion battery-type self-powered pressure sensor in this invention, and its rate performance at different current densities.

[0035] Figure 9 This is a schematic diagram of the battery characteristics of a flexible zinc-ion battery-type self-powered pressure sensor in an embodiment of the present invention. Detailed Implementation

[0036] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other.

[0037] In the description of this invention, it should be understood that the terms "center," "longitudinal," "lateral," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," and "outer," etc., indicating orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, are only for the convenience of describing the invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of the invention. Furthermore, the terms "first," "second," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined with "first," "second," etc., may explicitly or implicitly include one or more of that feature. In the description of this invention, unless otherwise stated, "a plurality of" means two or more.

[0038] In the description of this invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art will understand the specific meaning of the above terms in this invention based on the specific circumstances.

[0039] The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0040] like Figure 1 As shown, this invention provides a flexible zinc-ion battery-type self-powered pressure sensor, which, from top to bottom, includes a third electrode layer, an isolation layer, a self-supporting negative electrode layer, a gel electrolyte layer, and a positive electrode layer. The gel electrolyte is located between the positive electrode layer and the self-supporting negative electrode layer, with the side containing the active material in contact with the gel electrolyte. The isolation layer is located between the self-supporting negative electrode and the third electrode layer. When no pressure is applied, the third electrode layer and the negative electrode layer are not in contact due to the presence of the isolation layer, so the entire circuit is open. As the pressure increases, the contact area between the third electrode layer and the negative electrode layer increases, and the output voltage signal also increases, thereby realizing the conversion of electromechanical signals.

[0041] Specifically, such as Figure 2 As shown, the flexible positive electrode layer is formed by first coating an intermediate affinity layer ink on a flexible substrate, and then coating the positive electrode ink. This not only improves the conductivity but also provides excellent mechanical properties.

[0042] Specifically, an insulating layer is placed between the third electrode layer and the self-supporting negative electrode layer. The insulating layer is a porous foam sponge, which not only enables it to have a sensing mechanism but also provides a wide detection range.

[0043] Example 1

[0044] (1) Preparation of flexible positive electrode layer: Conductive carbon black, multi-walled carbon nanotubes and waterborne polyurethane (WPU) are added to a beaker at a weight ratio of 1:1:25 and stirred for 24 hours to prepare intermediate affinity layer ink. Then, it is poured into a mold with TPU as the flexible substrate and vacuum heated at 80°C for 2 hours in a drying oven. Waterborne polyurethane, TOCNF aqueous solution and isopropanol are added to a beaker at a volume ratio of 1:2.5:5 and stirred for 2 hours to prepare mixed solvent. Conductive carbon black, multi-walled carbon nanotubes, manganese dioxide and mixed solvent are added to a beaker at a weight ratio of 1.2:1.2:6:160 and stirred for 24 hours to prepare positive electrode ink. Then, it is poured on top of the heated intermediate affinity layer ink and vacuum heated at 80°C for 4 hours in a drying oven to finally obtain flexible positive electrode layer.

[0045] (2) Preparation of gel electrolyte: Graphene oxide solution, ethylene glycol, PVA, zinc chloride and deionized water were added to a beaker in a weight ratio of 1:2:2:4.6:15. The beaker mouth was then sealed with plastic wrap to prevent possible evaporation and exchange with external materials. The mixture was then stirred in a water bath with a magnetic stirrer at 95°C for 2 hours. The mixture was then poured into a petri dish and dried in a freeze dryer for 8 hours. Finally, the solidified gel electrolyte layer was peeled off from the petri dish.

[0046] (3) Preparation of a self-supporting negative electrode layer: Conductive carbon black, multi-walled carbon nanotubes and waterborne polyurethane (WPU) were added to a beaker at a weight ratio of 1:1:25 and stirred for 24 hours to prepare an intermediate affinity layer ink. The ink was then poured into a mold with a PET substrate and vacuum heated at 80°C for 2 hours in a drying oven. Waterborne polyurethane, TOCNF aqueous solution and isopropanol were added to a beaker at a volume ratio of 2:5:10 and stirred for 2 hours to prepare a mixed solvent. Conductive carbon black, multi-walled carbon nanotubes, zinc powder and the mixed solvent were added to a beaker at a weight ratio of 1.2:1.2:18:160 and stirred for 24 hours to prepare a negative electrode ink. The ink was then poured onto the heated intermediate affinity layer ink and vacuum heated at 80°C for 4 hours in a drying oven. Finally, the self-supporting negative electrode layer was peeled off from the PET film.

[0047] (4) Preparation of the third electrode layer: Conductive carbon black, multi-walled carbon nanotubes and waterborne polyurethane (WPU) are added to a beaker at a weight ratio of 1:1:25 and stirred for 24 hours to prepare the intermediate affinity layer ink. Then, it is poured into a mold with a flexible substrate of TPU and vacuum heated at 80°C for 2 hours in a drying oven.

[0048] (5) Figure 1 As shown, the third electrode layer, the isolation layer, the self-supporting negative electrode layer, the gel electrolyte layer, and the positive electrode layer are installed sequentially from top to bottom. The isolation layer is a 1mm porous sponge foam. Finally, a semi-cured PDMS solution is coated around the edges of each part for encapsulation.

[0049] Example 2

[0050] (1) Preparation of flexible positive electrode layer: Conductive carbon black, multi-walled carbon nanotubes and waterborne polyurethane (WPU) are added to a beaker at a weight ratio of 1:1:25 and stirred for 24 hours to prepare intermediate affinity layer ink. Then, it is poured into a mold with TPU as the flexible substrate and vacuum heated at 80°C for 2 hours in a drying oven. Waterborne polyurethane, TOCNF aqueous solution and isopropanol are added to a beaker at a volume ratio of 2:5:10 and stirred for 2 hours to prepare mixed solvent. Conductive carbon black, multi-walled carbon nanotubes, vanadium pentoxide (V2O5) and mixed solvent are added to a beaker at a weight ratio of 1.2:1.2:6:160 and stirred for 24 hours to prepare positive electrode ink. Then, it is poured on top of the heated intermediate affinity layer ink and vacuum heated at 80°C for 4 hours in a drying oven to finally obtain flexible positive electrode layer.

[0051] (2) Preparation of gel electrolyte: Graphene oxide solution, ethylene glycol, PVA, zinc chloride and deionized water were added to a beaker in a weight ratio of 1:2:2:4.6:15. The beaker mouth was then sealed with plastic wrap to prevent possible evaporation and exchange with external materials. The mixture was then stirred in a water bath with a magnetic stirrer at 95°C for 2 hours. The mixture was then poured into a petri dish and dried in a freeze dryer for 8 hours. Finally, the solidified gel electrolyte layer was peeled off from the petri dish.

[0052] (3) Preparation of a self-supporting negative electrode layer: Conductive carbon black, multi-walled carbon nanotubes and waterborne polyurethane (WPU) were added to a beaker in a weight ratio of 1:1:25 and stirred for 24 hours to prepare an intermediate affinity layer ink. The ink was then poured into a mold with a PET substrate and vacuum heated at 80°C for 2 hours in a drying oven. Waterborne polyurethane, TOCNF aqueous solution and isopropanol were added to a beaker in a volume ratio of 2:5:10 and stirred for 2 hours to prepare a mixed solvent. Conductive carbon black, multi-walled carbon nanotubes, zinc powder and the mixed solvent were added to a beaker in a weight ratio of 1.2:1.2:12:160 and stirred for 24 hours to prepare a negative electrode ink. The ink was then poured onto the heated intermediate affinity layer ink and vacuum heated at 80°C for 4 hours in a drying oven. Finally, the self-supporting negative electrode layer was peeled off from the PET film.

[0053] (4) Preparation of the third electrode layer: Conductive carbon black, multi-walled carbon nanotubes and waterborne polyurethane (WPU) are added to a beaker at a weight ratio of 1:1:25 and stirred for 24 hours to prepare the intermediate affinity layer ink. Then, it is poured into a mold with a flexible substrate of TPU and vacuum heated at 80°C for 2 hours in a drying oven.

[0054] (5) Install the third electrode layer, the isolation layer, the self-supporting negative electrode layer, the gel electrolyte layer, and the positive electrode layer in sequence from top to bottom. The isolation layer is a 1mm porous sponge foam. Finally, apply a semi-cured PDMS solution around the edges of each part for encapsulation.

[0055] Example 3

[0056] (1) Preparation of flexible positive electrode layer: Conductive carbon black, multi-walled carbon nanotubes and waterborne polyurethane (WPU) are added to a beaker at a weight ratio of 1:1:25 and stirred for 24 hours to prepare intermediate affinity layer ink. Then, it is poured into a mold with TPU as the flexible substrate and vacuum heated at 80°C for 2 hours in a drying oven. Waterborne polyurethane, TOCNF aqueous solution and isopropanol are added to a beaker at a volume ratio of 2:5:10 and stirred for 2 hours to prepare mixed solvent. Conductive carbon black, multi-walled carbon nanotubes, manganese dioxide and mixed solvent are added to a beaker at a weight ratio of 1.2:1.2:6:160 and stirred for 24 hours to prepare positive electrode ink. Then, it is poured on top of the heated intermediate affinity layer ink and vacuum heated at 80°C for 4 hours in a drying oven to finally obtain flexible positive electrode layer.

[0057] (2) Preparation of gel electrolyte: Graphene oxide solution, ethylene glycol, PVA, zinc chloride and deionized water were added to a beaker in a weight ratio of 1:2:2:4.6:15. The beaker mouth was then sealed with plastic wrap to prevent possible evaporation and exchange with external materials. The mixture was then stirred in a water bath with a magnetic stirrer at 95°C for 2 hours. The mixture was then poured into a petri dish and dried in a freeze dryer for 8 hours. Finally, the solidified gel electrolyte layer was peeled off from the petri dish.

[0058] (3) Preparation of a self-supporting negative electrode layer: Conductive carbon black, multi-walled carbon nanotubes and waterborne polyurethane (WPU) were added to a beaker in a weight ratio of 1:1:25 and stirred for 24 hours to prepare an intermediate affinity layer ink. The ink was then poured into a mold with a PET substrate and vacuum heated in an oven at 80°C for 2 hours. Waterborne polyurethane, TOCNF aqueous solution and isopropanol were added to a beaker in a volume ratio of 2:5:10 and stirred for 2 hours to prepare a mixed solvent. Conductive carbon black, multi-walled carbon nanotubes, zinc powder and viscous solvent were added to a beaker in a weight ratio of 1.2:1.2:18:160 and stirred for 24 hours to prepare a negative electrode ink. The ink was then poured onto the heated intermediate affinity layer ink and vacuum heated in an oven at 80°C for 4 hours. Finally, the self-supporting negative electrode layer was peeled off from the PET film.

[0059] (4) Preparation of the third electrode layer: Conductive carbon black, multi-walled carbon nanotubes and waterborne polyurethane (WPU) are added to a beaker at a weight ratio of 1:1:25 and stirred for 24 hours to prepare the intermediate affinity layer ink. Then, it is poured into a mold with a flexible substrate of TPU and vacuum heated at 80°C for 2 hours in a drying oven.

[0060] (5) Install the third electrode layer, the isolation layer, the self-supporting negative electrode layer, the gel electrolyte layer and the positive electrode layer in sequence from top to bottom. The isolation layer is a 0.5mm porous sponge foam. Finally, apply a semi-cured PDMS solution around the edges of each part for encapsulation.

[0061] Comparative Example 1

[0062] In this embodiment, the sensor structure installation sequence in step 5, which involves "installing the third electrode layer, the isolation layer, the self-supporting negative electrode layer, the gel electrolyte layer, and the positive electrode layer sequentially from top to bottom, wherein the isolation layer is a 2mm porous sponge foam," is replaced with "installing the negative electrode layer, the isolation layer, the gel electrolyte, and the positive electrode layer sequentially from top to bottom, wherein the isolation layer is a 2mm porous sponge foam." The third electrode layer is not required, and all other conditions are the same as in embodiment 3. Table 1 shows the sensors with different cycle stability and sensitivity obtained from different assembly sequences.

[0063] Table 1

[0064]

[0065] Comparative Example 1 illustrates that when the separator layer is in direct contact with the gel electrolyte layer, since the gel electrolyte layer is mostly adhesive and contains a small amount of water, when pressure is applied, the water in the gel electrolyte layer will seep into the separator layer, causing the battery to directly reach the open circuit voltage. When the pressure is removed, the gel electrolyte adheres to the electrode, causing the sensor to fail to bounce back, and ultimately the sensor fails.

[0066] like Figure 4 The image shown is a physical diagram of the flexible electrode and sensor in an embodiment of the present invention; specifically, the flexible electrode has excellent mechanical properties and can be stretched, while the assembled sensor also has flexibility and can be bent.

[0067] like Figure 5-8 The diagram shown illustrates the performance test of the flexible zinc-ion battery-type self-powered pressure sensor according to an embodiment of the present invention. The fabricated pressure sensor exhibits excellent sensing performance. When the pressure range is 0-50 kPa, the sensitivity is 19.5 mV / kPa. -1 The sensitivity is 1.62 mV KPa in the pressure range of 50-310 kPa. -1 It also has good stability.

[0068] like Figure 9 The figure shows the battery characteristics of the flexible zinc-ion battery-type self-powered pressure sensor in this embodiment of the invention, displaying its rate performance at different current densities. When the current density recovers to 0.1 A g... -1 At that time, the discharge specific capacity can be restored to its original level.

[0069] The flexible zinc-ion battery-type self-powered pressure sensor prepared in this invention can be used not only as a pressure sensor but also as an energy storage device. Compared with sensors that require external power and multiple integrated components, the flexible zinc-ion battery-type self-powered pressure sensor has the advantages of small size and low cost, and can overcome the limitation of current piezoelectric and triboelectric self-powered pressure sensors, which can usually only detect dynamic pressure.

[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for fabricating a flexible zinc-ion battery-type self-powered pressure sensor, characterized in that: A flexible zinc-ion battery-type self-powered pressure sensor includes a positive electrode layer, a gel electrolyte layer, a self-supporting negative electrode layer, an isolation layer, and a third electrode layer. The gel electrolyte layer is located between the positive electrode layer and the self-supporting negative electrode layer. The isolation layer is located between the self-supporting negative electrode layer and the third electrode layer. The self-supporting negative electrode layer is disposed below the isolation layer. The positive electrode layer is at least one of copper foil, capacitive electrode material ink coated on a conductive current collector, or metal oxide ink coated on a conductive current collector. The capacitive electrode material is at least one of activated carbon (AC), carbon nanotubes (CNTs), graphene, and carbon fiber. The metal oxide is at least one of MnO2, RuO2, and V2O5. The conductive current collector is at least one of stainless steel foil, stainless steel mesh, and a flexible conductive elastomer substrate. The self-supporting negative electrode layer is a flexible self-supporting zinc negative electrode layer. The isolation layer is an electrospun fiber film or porous sponge foam with a thickness of 0.2 mm to 2 mm. The preparation method includes the following steps: (1) Preparation of intermediate affinity layer ink; Conductive carbon black and multi-walled carbon nanotubes are ground and then poured into waterborne polyurethane and stirred. The weight ratio of conductive carbon black, multi-walled carbon nanotubes and waterborne polyurethane is (0.5~2):1:(1.5~3.5). (2) Preparation of the positive electrode layer; First, the positive electrode ink is prepared by grinding conductive carbon black, multi-walled carbon nanotubes, and manganese dioxide. Then, it is poured into a mixed solvent composed of aqueous polyurethane, TOCNF aqueous solution, and isopropanol and stirred. The weight ratio of conductive carbon black, multi-walled carbon nanotubes, and manganese dioxide is 1:1:(5.5-9.5), and the volume ratio of aqueous polyurethane, TOCNF aqueous solution, and isopropanol is (1-2.5):(4-6):(8-12). The weight ratio of conductive carbon black, multi-walled carbon nanotubes, manganese dioxide, and mixed solvent is 1:1:(5.5-9.5):(93-110). Next, the mold is prepared by placing a high-temperature resistant polyester film (PET) in a laser cutting machine to process the mold into the required shape. A piece of flexible substrate is cut off, and the PET mold is tightly attached to the flexible substrate. Then, the intermediate affinity layer ink is poured into the mold prepared from PET. After vacuum heating in a drying oven, the positive electrode ink is poured on the intermediate affinity layer and vacuum heating is continued in the drying oven. (3) Preparation of a self-supporting negative electrode layer; First, the negative electrode ink is prepared by grinding conductive carbon black, multi-walled carbon nanotubes, and zinc powder. Then, it is poured into a solvent composed of aqueous polyurethane, TOCNF aqueous solution, and isopropanol and stirred. The weight ratio of conductive carbon black, multi-walled carbon nanotubes, and zinc powder is 1:1:(9.5-25), and the volume ratio of aqueous polyurethane, TOCNF aqueous solution, and isopropanol is (1-2.5):(4-6):(8-12). The weight ratio of conductive carbon black, multi-walled carbon nanotubes, zinc powder, and mixed solvent is 1:1:(9.5-25):(93-110). Next, the mold is prepared by placing high-temperature resistant polyester film (PET) in a laser cutting machine to process the mold into the required shape. A piece of flexible substrate is cut off, and the PET mold is tightly attached to the flexible substrate. Then, the intermediate affinity layer ink is poured into the mold prepared from PET. After vacuum heating in a drying oven, the negative electrode ink is poured on the intermediate affinity layer and vacuum heating is continued in the drying oven. (4) Preparation of gel electrolytes; PVA, zinc chloride, ethylene glycol and graphene oxide solution were poured into deionized water and stirred in a 95°C water bath for 2 hours. (5) Fabrication of the third electrode layer; The intermediate affinity layer ink is poured into a mold made of PET and then vacuum heated in a drying oven; (6) Place the third electrode layer, the isolation layer, the self-supporting zinc negative electrode layer, the gel electrolyte layer and the positive electrode layer in sequence from top to bottom, and coat the edges of each part with a semi-cured PDMS solution for encapsulation.

2. An application of a flexible zinc-ion battery-type self-powered pressure sensor, characterized in that: The flexible zinc-ion battery type self-powered pressure sensor is obtained by the preparation method of claim 1, and the flexible zinc-ion battery type self-powered pressure sensor is used in wearable devices.